Pemaafan pada Kasus Korban Penyiraman Air Keras - Sarah Kiftia Zelhas; Vinaya; Whinda Yustisia (Jurnal Ilmiah Psikologi MIND SET, 2016)
This research aims to find out the description of forgiveness and factors that influence forgiveness of the victim of basin hydrochloric water. The research used qualitative methods and the participant is a male, 16 years old, who became the worst and youngest victim of the basin hydrochloric water in the case of PPD bus. The result showed that the factors influenced the process of forgiveness is due to wound inflicted by offender, rumination about the accident, and closeness of relationship with the offender. Participant has reached the work phase, the third step in four steps of forgiveness. Although the participant has started to forgive, he did not completely forgive the offender, and couldn't forget the incident yet.